Systematic review in financialization politics: The role of corporate governance and managerial compensation - Vieira, R.; Azevedo, G.; Oliveira, J. (International Journal of Disclosure and Governance, 2024)
This review seeks to synthesize empirical findings on financialization policies and provide answers to two questions: (1) What relationship exists between Financialization and Corporate Governance? (2) Is there any relationship between financialization and CEO compensation/remuneration systems? A group of 38 scientific articles was selected using the methodological protocols ProKnow-C and Methodi Ordinatio. Based on its reading, analysis, and synthesis of the main empirical findings between financialization and the accumulation of capital and between financialization and income distribution, it is evident that there is a negative correlation between this phenomenon and the investment in means of production and the proportion of income from labour. We hope that this work can contribute to a rethinking of the income redistribution model (internationally), as the current model has contributed to an increase in the unequal distribution of social wealth, which is characterized primarily by the excessive compensation of top executives who prioritize short-term goals. We hope that it can also serve as a foundation for future scientific work and as a resource not only for regulatory agencies but also for government entities that must make political, economic, and fiscal decisions to mitigate or even reverse the global effects.